(3c-3)(4c+8)=

Simple and best practice solution for (3c-3)(4c+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3c-3)(4c+8)= equation:


Simplifying
(3c + -3)(4c + 8) = 0

Reorder the terms:
(-3 + 3c)(4c + 8) = 0

Reorder the terms:
(-3 + 3c)(8 + 4c) = 0

Multiply (-3 + 3c) * (8 + 4c)
(-3(8 + 4c) + 3c * (8 + 4c)) = 0
((8 * -3 + 4c * -3) + 3c * (8 + 4c)) = 0
((-24 + -12c) + 3c * (8 + 4c)) = 0
(-24 + -12c + (8 * 3c + 4c * 3c)) = 0
(-24 + -12c + (24c + 12c2)) = 0

Combine like terms: -12c + 24c = 12c
(-24 + 12c + 12c2) = 0

Solving
-24 + 12c + 12c2 = 0

Solving for variable 'c'.

Factor out the Greatest Common Factor (GCF), '12'.
12(-2 + c + c2) = 0

Factor a trinomial.
12((-2 + -1c)(1 + -1c)) = 0

Ignore the factor 12.

Subproblem 1

Set the factor '(-2 + -1c)' equal to zero and attempt to solve: Simplifying -2 + -1c = 0 Solving -2 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1c = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1c = 0 + 2 -1c = 0 + 2 Combine like terms: 0 + 2 = 2 -1c = 2 Divide each side by '-1'. c = -2 Simplifying c = -2

Subproblem 2

Set the factor '(1 + -1c)' equal to zero and attempt to solve: Simplifying 1 + -1c = 0 Solving 1 + -1c = 0 Move all terms containing c to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1c = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1c = 0 + -1 -1c = 0 + -1 Combine like terms: 0 + -1 = -1 -1c = -1 Divide each side by '-1'. c = 1 Simplifying c = 1

Solution

c = {-2, 1}

See similar equations:

| 8w+6=-2(w-7) | | lx+3l=3x+6 | | 3(x+5)-2x=15 | | 6x-77+2x=43 | | -16/9=-8u | | 7x-2(1+3x)=2 | | 18+5w=3w-10 | | 5y-3/5=4/3 | | -(3v+4)=6v-3(3v+2) | | 77+4x=43 | | -2x(3x+4)+y=0 | | 0+1x=0.2(x+2) | | 3W-6+6W=-2+W | | -2/3t=6 | | 5x-x=12+6x | | 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 | | 4(x-5)+4(x-5)+3(x+6)+3(x+6)= | | 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= | | 5(x-3)=-(15-5x) | | -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) |

Equations solver categories